2017
DOI: 10.3390/nu9070708
|View full text |Cite|
|
Sign up to set email alerts
|

Dietary Chlorella vulgaris Ameliorates Altered Immunomodulatory Functions in Cyclophosphamide-Induced Immunosuppressive Mice

Abstract: Based on the well-known toxicity of cyclophosphamide (CYP) on the immune system, this research investigated the modulating effects of the long-term dietary Chlorella vulgaris (CV) supplementation on the immunosuppression induced by CYP in mice, in order to provide a novel dietary design to mitigate the side effects of CYP therapy. Control, CYP-treated, CYP + CV (6%), CYP + CV (12%) and CYP + CV (24%) were used for 6 weeks, CV supplement in diet recovered the significantly reduced immunological function in CYP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Macrophages, an important type of immune cell, have a key role in the immune response and host defense, and mediate inflammation in non-specific immunity by phagocytosis to kill and clear away pathogens and foreign bodies ( 22 , 23 ). It is known that Cyp significantly lowers the phagocytosis of mouse macrophages ( 2 ). The present study indicated that SCP significantly preserves the function of macrophages of Cyp-induced immunocompromised mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages, an important type of immune cell, have a key role in the immune response and host defense, and mediate inflammation in non-specific immunity by phagocytosis to kill and clear away pathogens and foreign bodies ( 22 , 23 ). It is known that Cyp significantly lowers the phagocytosis of mouse macrophages ( 2 ). The present study indicated that SCP significantly preserves the function of macrophages of Cyp-induced immunocompromised mice.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant tumors are a serious threat to the health of patients and a burden on their families and society. Cyclophosphamide (Cyp) is one of the most widely used chemotherapeutic drugs for the treatment of malignant tumors, but due to its severe immunosuppressive adverse effect ( 1 , 2 ), it is necessary to co-administer drugs with immunomodulatory function and food supplements with an immune-regulating function.…”
Section: Introductionmentioning
confidence: 99%
“…Besides their value as protein and lipid sources, microalgae are also being considered for their health-promoting potential, as they are a rich source of bioactive compounds, such as pigments, vitamins, minerals, and antioxidants (14). These bioactive compounds are reported to have a high spectrum of biological functions, including anti-inflammatory, immunomodulatory, antioxidant, and antibacterial activities (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…The avasimibe and CTX+avasimibe group exhibited increased spleen weights and spleen index values compared with the control group, but these values were higher in the avasimibe treatment group compared with the CTX+avasimibe group, which may be due to the effects of CTX on the immune system in these mice. CTX is commonly used as an immunosuppressant to inhibit tumor growth, which may inhibit immune system function (4345). Furthermore, the inhibition of ACAT-1 by avasimibe may improve the immune function in mice (38,41,42).…”
Section: Discussionmentioning
confidence: 99%